1996
DOI: 10.1136/jcp.49.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of apoptosis with tumour cell differentiation, progression, and HPV infection in cervical carcinoma.

Abstract: Aims-To clarify the significance of apoptosis in the progression of uterine cervical neoplasias, including cervical intraepithelial neoplasia (CIN), microinvasive carcinoma (MIC), and invasive squamous cell carcinoma (ISCC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 32 publications
(4 reference statements)
6
38
2
Order By: Relevance
“…In a previous study, we noted that the majority of Bcl-2-negative invasive tumours were accompanied by Bcl-2-negative DCIS (H-J. van (Lipponen and Aaltomaa, 1994;Aihara et al, 1995;Du et al, 1996;Isacson et al, 1996;Koshida et al, 1996;Shoji et al, 1996). For instance, in gastric cancer, Bcl-2 expression was positively correlated with a low Al and MI, whereas Bax expression seemed to be correlated with an increased AI and MI.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we noted that the majority of Bcl-2-negative invasive tumours were accompanied by Bcl-2-negative DCIS (H-J. van (Lipponen and Aaltomaa, 1994;Aihara et al, 1995;Du et al, 1996;Isacson et al, 1996;Koshida et al, 1996;Shoji et al, 1996). For instance, in gastric cancer, Bcl-2 expression was positively correlated with a low Al and MI, whereas Bax expression seemed to be correlated with an increased AI and MI.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the possibility was excluded by comparing the TllNEL-positive cells with histological findings, including inflammation in H&E-stained sections. p53, HPV and apoptosis in oral carcinorma 359 various locations, which ranged from 1.5 to 10.9 (Kasagi et al, 1994;Shoji et al, 1996;Tatebe et al, 1996). In relation to p53 status, SCCs associated with p53 mutation had significantly lower Al than those with wild-type p53 (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in vitro experiments demonstrating apoptosis and IL-1a release from keratinocytes expressing high levels of E6 and E7 genes from retroviral vectors may be biologically relevant and representative of HSIL or carcinoma where E6 and E7 genes are integrated and transcriptionally upregulated (DuÈ rst et al, 1992;Stoler et al, 1992). Previous studies have shown that apoptosis is increased in HSIL and cervical carcinoma (Isacson et al, 1996;Shoji et al, 1996) and correlates with increased cellular proliferation rather than with`low or high risk' HPV types (Isacson et al, 1996). Our results con®rm these observations and extend them by suggesting that the extent of apoptosis is related to levels of HPV RNA expression.…”
Section: Discussionmentioning
confidence: 99%